Barriers to HPV Vaccination Among Unvaccinated, Haitian American College Women - Dudith Pierre-Victor; Dionne P. Stephens; Angela Omondi; Rachel Clarke; Naomie Jean-Baptiste; Purnima Madhivanan (Mary Ann Liebert, 2018)
Background: Haitian women residing in the United States are disproportionately affected by cervical cancer. Human papillomavirus (HPV) vaccine has been licensed in the United States since 2006. Vaccination rates are less than optimal overall, and the rates are particularly low among young black women. We investigated barriers to HPV vaccination in a sample of Haitian American college women. Methods: Thirty self-identified Haitian American women, aged 17?26 years, were recruited from a large university campus in southeastern United States (n=30). They completed in-depth face-to-face interviews. The research team analyzed the transcripts using thematic analysis. Results: More than half of the participants (n=18) had not yet initiated the HPV vaccine series. Most of the unvaccinated participants stated that they had received a provider recommendation for the vaccine. Lack of provider recommendation, negative vaccine perception and attitudes, and side effect concerns constituted barriers to vaccination. Conclusions: Haitian American college women at high risk of cervical cancer have cited several barriers to HPV vaccination, with the most prominent being lack of physician recommendation. Healthcare providers should continue recommending the vaccine to college women as many of them may not have received a recommendation. When recommending the HPV vaccine, discussions should be framed with the intent to positively influence HPV vaccine perceptions and ultimately vaccine attitudes.